Prevalence and risk factors for low vitamin D status among breastfeeding mother–infant dyads in an environment with abundant sunshine - Salameh K; Al-Janahi NS; Reedy AM; Dawodu A (Dove Medical Press, 2016)
Khalil Salameh,1 Najah Saleh Ali Al-Janahi,2 Adriana M Reedy,3 Adekunle Dawodu3 1Division of Pediatrics, Al-Wakra Hospital, Hamad Medical Corporation, 2Department of Obstetrics and Gynecology, Women’s Hospital, Hamad Medical Corporation, Doha, Qatar; 3Global Health Center, Cincinnati Children’s Hospital Medical Center, Cincinnati, OH, USA Purpose: Evaluation of vitamin D (vD) status and risk factors for low vD among breastfeeding mother–infant dyads in a population at high risk for vD deficiency.Subjects and methods: We measured serum 25-hydroxyvitamin D (25(OH)D) and parathyroid hormone at 1 month postpartum in 60 consecutive exclusively breastfeeding Arab mother–infant dyads enrolled in a high dose vD supplementation study to prevent vD deficiency in Doha, Qatar, (latitude 25°N) during summer months. Data were collected on demography, sun exposure, and vD supplementation. Comparison with a US cohort was evaluated. vD deficiency was defined as serum 25(OH)D <50 nmol/L and severe deficiency categorized as 25(OH)D <25 nmol/L in mothers and infants.Results: Mean maternal age was 29 years and 77% had college or university education. Maternal median 25(OH)D was 32.5 nmol/L and 78% were vD-deficient and 20% had 25(OH)D <25 nmol/L. Only 42% of mothers had reportedly taken vD supplements postpartum and median dietary vD intake (119 IU/day) and calcium (490 mg/day) were low. Maternal median sun index score (sun exposure [hours/week] × body surface area exposed while outdoors) was 0. Maternal 25(OH)D correlated with percent body surface area exposure while outdoors (rs=0.37, P=0.004). Infant median 25(OH)D was 20 nmol/L and 83% were deficient, while 58% had 25(OH)D <25 nmol/L. Infant 25(OH)D correlated with maternal levels (rs=0.41, P=0.001). None of the infants received vD supplement at 1 month of age and median sun index score was 0. Infant’s parathyroid hormone showed negative correlations with 25(OH)D (rs=-0.28, P=0.03). Sun exposure, vD supplementation rate, and vD status were lower in Doha than Cincinnati, US cohort.  Conclusion: vD deficiency is common in breastfeeding mother–infant dyads in this sunny environment and is associated with sun avoidance and low vD intake. We suggest corrective vD supplement of breastfeeding mothers and their infants, which should preferably start during pregnancy. Keywords: vitamin D deficiency, lactation, mothers, infants, sunlight exposure